Pengaruh Pemberian Ekstrak Kulit Manggis (Garcinia mangostana L.) dalam Mencegah Kerusakan Histopatologi Ginjal Tikus Putih (Rattus norvegicus) yang Diinduksi Gentamisin - Rio Nanda Pratama; Ratih Puspita Febrinasari; Nur Hafidha Hikmayani (Nexus Biomedika, 2014)
Background: The use of medicinal plants has been increasing in recent years following development of herbal industry and evidence on adverse effects of several chemical drugs, including nephrotoxic effect. Research on herbs with nephroprotective effect are needed to offer alternative therapy for drug-induced renal diseases. Mangosteen pericarp extract contains xanthone which has antiinflammation effect to prevent renal damages. This research aimed to examine the nephroprotective effect of mangosteen pericarp extract on renal structure. Methods: This research was a laboratory experiment with posttest only controlled group design. Subjects were white male Wistar-strain rats (Rattus norvegicus), aged 2-3 months and weighed 150-230 grams. Subjects were randomly divided into five treatment groups. Normal control group was treated 0.5% NaCMC, while negative control group was treated nothing. The treatment groups 1, 2 and 3 were treated with extract of mangosteen pericarp at doses of 62.5 mg/kg-BW, 125 mg/kg-BW, and 250 mg/kg-BW, respectively. The treatments were maintained for 2 weeks. In the second week, the negative control group and the treatment groups 1, 2, and 3 were induced by gentamicin 100 mg/kg-BW. The subjects were later terminated and their kidneys were stained with hematoxicylin eosin. Histopathological renal damages were semi-quantitatively assessed by identification of pyknotic, karyorrhexic and karyolytic areas in proximal tubulus cells and were compared using one-way ANOVA test and followed by LSD test. Result: Result of one-way ANOVA test showed that proximal tubulus cellular damage differed significantly across five groups (p < 0.001). LSD tests further showed a significant difference between negative control group and other groups (p < 0.001). Renal damage in normal control group also differed significantly from those of treatment group 1 and 3 (p < 0.001). No significant difference was found between normal control group and treatment group 2 (p = 0.972). Conclusion: Mangosteen (Garcinia mangostana L.) pericarp extract could prevent histopathological renal damage in white rats (Rattus norvegicus) induced gentamicin. Keywords: Mangosteen pericarp extract, Renal histopathology, Gentamicin.